2008
DOI: 10.1021/jp800350v
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Insulin Chain-B in Isolated and Monomeric Environments under External Stress

Abstract: We have conducted a series of theoretical simulations of insulin chain-B under different electric field conditions. This work extends our previous studies of the isolated chain-B by including chain-A and revealing the effects of chemical stress. For this complete protein, we observed increased stability under ambient conditions and under the application of thermal stress, compared to isolated chain-B. On the other hand, the presence of chain-A enhanced the effects of the applied electric field. Under the stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 42 publications
1
50
0
Order By: Relevance
“…47 Additionally, analysis of the SASA of proteins can be used to provide useful information of the protein potential ability to interact with the solvent and with others proteins. 47,48 As shown in Figure 5, the presence of the external field induced not only changes in the dipole moment but also significant increases in the SASA. Also in line with the trend in the flexibility of the proteins, it was observed that the potential induced larger changes in the SASA for Mb than for LSZ.…”
Section: Resultsmentioning
confidence: 99%
“…47 Additionally, analysis of the SASA of proteins can be used to provide useful information of the protein potential ability to interact with the solvent and with others proteins. 47,48 As shown in Figure 5, the presence of the external field induced not only changes in the dipole moment but also significant increases in the SASA. Also in line with the trend in the flexibility of the proteins, it was observed that the potential induced larger changes in the SASA for Mb than for LSZ.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown that electromagnetic radiation influences the glucose concentration, dielectric and electrical properties of the blood [29,30]. Electric field effect on insulin chain-B under static and oscillating conditions showed that the electric field caused a destabilizing effect on the peptide [31][32][33]. However, not much work has been done on the effects of cellular phone radiation at 850 MHz on the diabetic blood cells.…”
Section: Introductionmentioning
confidence: 99%
“…field strength of greater than 0.01 V/Å is required to perturb the zero field behavior of these molecules. [7–14] The presence of a field perturbs conformational states, due to localized residue‐specific dipolar orientation with the field altering hydrogen bonding arrangement dynamics and secondary and tertiary structure motifs, and enhancing sampling of peptide energy landscape as a result. The more rapid structural changes corresponding to shorter‐lived secondary and tertiary contacts increase the backbone fluctuations, rendering the more globular state of the peptide entropically and energetically favored.…”
Section: Discussionmentioning
confidence: 99%
“…[2–6] Bearing this in mind, molecular simulation provides one possible avenue for the unambiguous study of such effects. Recent work in this group,[7–9] as well as others,[10–14] has examined the athermal effects of electric and e/m fields on the structural stability of several enzymes and peptides. The hen egg white lysozyme (HEWL) simulations demonstrated the good stability of the enzyme across a range of field strengths and frequencies with field strengths in the region of 0.05 V/Å or greater required to disrupt the secondary structure of the protein (via perturbation of intra‐protein hydrogen bonds).…”
Section: Introductionmentioning
confidence: 99%